Applied Nanotechnology. - Ramsden, Jeremy (Elsevier, 2009)
This book joins, for the first time, technical nanotechnology information with the non-technical to explain the fundamentals -- with an emphasis on a succinct set of principles. It takes a "first principles" look at the economics of converting research results to products, highly important due to the potentially disruptive nature of nanotechnology. How nanotechnology builds on earlier technologies is shown while introducing its own unique paradoxes. The book surveys what has actually been realized, comparing laboratory achievements with commercially successful products, and offers a
Keywords: Nanotechnology.; Nanostructured materials industry.; elektronické knihy; electronic books